Manejo del insecto plaga de Nezara viridula L, 1758 (Hemiptera: Pentatomidae) en el cultivo de la soya (Glycine max) - Nivela Echeverria, Hugo Francisco (2023)
In this study, information was collected on aspects related to the management of the pest insect Nezara viridula L; The different cultural, chemical and biological control alternatives were described to control the incidence of the effects caused by it. Soybeans are an important crop in Ecuador, with a planting area of 27,960.01 hectares. Likewise, it provides access to various products in the agricultural sector, which generates greater use and profitability in the planting of transitional crops in Ecuador on an economic and social scale. The Management of this N. viridula allows the damage caused by this pest to reach levels much lower than economically sustainable. IPM is a combination of control measures designed to address the risks that agricultural development allows for sustainability and sustainability for human health as well as care for the environment. The soybean or green bug is a pest insect that feeds mainly in the pod formation stage (R3 and R4); Likewise, the development of N. viridula from egg to adult is subject to climatic factors and can take between 3 and 10 weeks.